2021
DOI: 10.1093/heapro/daab140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a social media-based counselling intervention in countering fake news on COVID-19 vaccine in Nigeria

Abstract: Summary The aim of this study was to understand the impact of counselling in countering fake news-related COVID-19 vaccine. We conducted two separate experiments. In the first experiment, we exposed the treatment group to fake news on COVID-19 vaccine through a WhatsApp group chat while the control group was not. We then tested the effectiveness of such fake news on their perception. In our second experiment, we exposed the treatment group to a social media-based counselling intervention wherein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Other rumours with serious negative implications for people’s perception of COVID-19 included notions that persons who receive the vaccine will die within two years, that the COVID-19 vaccine will alter people’s DNA, that the vaccine was developed in a hurry and cannot be trusted, that the vaccine has serious negative side effects, that the vaccine contains a chip, that the vaccine is ineffective, and that the vaccine is unsuitable for Black people in general [ 46 ]. Some indicated the former president of the USA urged Black African people not to accept vaccines from Europe [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other rumours with serious negative implications for people’s perception of COVID-19 included notions that persons who receive the vaccine will die within two years, that the COVID-19 vaccine will alter people’s DNA, that the vaccine was developed in a hurry and cannot be trusted, that the vaccine has serious negative side effects, that the vaccine contains a chip, that the vaccine is ineffective, and that the vaccine is unsuitable for Black people in general [ 46 ]. Some indicated the former president of the USA urged Black African people not to accept vaccines from Europe [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…This review identified three studies that sought to identify measures that could address COVID-19 misinformation [ 30 , 46 , 47 ]. To counter misinformation via WhatsApp in Zimbabwe [ 30 ], researchers partnered with established and trusted organizations such as Internews and Kubatana.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that the best way to deal with vaccine hesitancy and enhance vaccine acceptance among the population is to employ factors that affect vaccine acceptance, such as gender, age, education level, beliefs in conspiracy theories and psychosocial factors. For example, psychological counseling can be used to counter fake news in the context of these factors ( Atehortua and Patino, 2021 ; Talabi et al , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Women in these four countries were more likely to reject the vaccine due to mistrust of information from mainstream media which are usually channeled through the state-government institutions. Widespread false information about the health risks associated with taking the vaccine through social media also further adds to the public's fear as seen in Nigeria [33] and Taiwan [34].…”
Section: Introductionmentioning
confidence: 99%